2023
DOI: 10.3847/2041-8213/aca9d0
|View full text |Cite
|
Sign up to set email alerts
|

JWST’s PEARLS: A JWST/NIRCam View of ALMA Sources

Abstract: We report the results of James Webb Space Telescope/NIRCam observations of 19 (sub)millimeter sources detected by the Atacama Large Millimeter Array (ALMA). The accurate ALMA positions allowed unambiguous identifications of their NIRCam counterparts. Taking gravitational lensing into account, these represent 16 distinct galaxies in three fields and constitute the largest sample of its kind to date. The counterparts’ spectral energy distributions cover from rest-frame ultraviolet to near-IR and provide photomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…System 24 (El Anzuelo) is not included in the set of constraints for the spectroscopic model, and the member galaxies constraining this model are completely unconstrained making impossible any redshift prediction for this system. The assigned redshift corresponds to the photometric redshift derived by Cheng et al (2023). The redshift of system 53 is unconstrained by the lens model, indicating a possible issue with this system, which is close to a spiral member galaxy.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…System 24 (El Anzuelo) is not included in the set of constraints for the spectroscopic model, and the member galaxies constraining this model are completely unconstrained making impossible any redshift prediction for this system. The assigned redshift corresponds to the photometric redshift derived by Cheng et al (2023). The redshift of system 53 is unconstrained by the lens model, indicating a possible issue with this system, which is close to a spiral member galaxy.…”
Section: Discussionmentioning
confidence: 65%
“…The red nucleus of the extended background galaxy is lensed into at least three images clearly visible in the reddest JWST bands. The three images of the nucleus coincide with the position of Atacama Large Millimeter/submillimeter Array (ALMA) sources EG-SMG 2 and EG-SMG 4 (Cheng et al 2023), the latter containing two images barely resolved by ALMA. Previous HST data did not show El Anzuelo as multiply lensed because this galaxy is red and therefore faint at wavelengths shorter than 1.6 µm.…”
Section: Jwst Datamentioning
confidence: 63%
“…When available, we look for counterparts at long wavelengths to exclude obvious dusty interlopers. We search for matches in submillimetric observations in CEERS (450 and 850 μm with SCUBA-2; Geach et al 2017;Zavala et al 2017), PRIMER (870 μm with the Atacama Large Millimeter/ submillimeter Array (ALMA) from the AS2UDS survey; Dudzevičiūtė et al 2020, andCheng et al 2023), and SMACS 0723 (1.1 mm with ALMA from the ALCS Survey; Kokorev et al 2022;Fujimoto et al 2023). We found only one potential association with a ∼5σ SCUBA-2 detection at 850 μm in CEERS (S2CLS-EGS-850.063 in Zavala et al 2017, #9329 in our catalog).…”
Section: Dusty Star-forming or High-redshift Contaminantsmentioning
confidence: 99%
“…We cross-checked our list of candidate quiescent objects with available catalogs of submillimetric surveys in CEERS (450 and 850 μm down to σ 450 = 1.2 and σ 850 = 0.2 mJy beam −1 with SCUBA-2 in the deep tier of the S2CLS survey, Zavala et al 2017; σ 850 = 1.2 mJy beam −1 over the full survey, Geach et al 2017), PRIMER (870 μm with ALMA from the AS2UDS survey targeting SCUBA-2 submillimeter galaxies from the S2CLS survey, Geach et al 2017; and detecting sources as faint as 0.6 mJy at >4.3σ, Dudzevičiūtė et al 2020;Cheng et al 2023, based on a combination of archival data), and SMACS 0723 (1.1 mm observations with σ 1.1mm = 66.1 μJy beam −1 from ALMA in the context of the ALCS Survey; Kokorev et al 2022;Fujimoto et al 2023). These limits correspond to SFR = 33 − 26 (CEERS/S2CLS-deep), 200-150 (S2CLS shallow); 25-19 (PRIMER/AS2UDS), 130-102 (S2CLS), and 25-16 M e yr −1 (SMACS 0723/ALCS) at z = 3-6, obtained by rescaling the 1σ rms with a modified blackbody with temperature T dust = 40 K, β = 2, k 0 = 0.43 cm 2 g −1 at λ 0 = 850 μm (Li & Draine 2001), and accounting for the lesser effect of the cosmic microwave background (da Cunha et al 2013).…”
Section: B3 Submillimetric Coverage and Spectroscopically Confirmed O...mentioning
confidence: 99%
“…A prime opportunity for using JWST to map the assembly of stellar mass at high-redshift is with the Prime Extragalactic Areas for Reionization and Lensing Science (PEARLS) program, which targets seven massive lensing clusters (Windhorst et al 2023). One such cluster, ACT-CL J0102-4915, or "El Gordo" (Menanteau et al 2012), has been identified as a foreground for a rich galaxy group at z=4.3 (Caputi et al 2021;Frye et al 2023), including DSFGs (see also Cheng et al 2023). In this work, we focus on an extraordinary, recently-discovered lensed DSFG J010249-491507 (shown in Fig.…”
Section: Introductionmentioning
confidence: 97%